Characterization and analysis of scFv-IgG bispecific antibody size variants. Issue 8 (17th November 2018) - Cao, Mingyan; Wang, Chunlei; Chung, Wai Keen; Motabar, Dana; Wang, Jihong; Christian, Elizabeth; Lin, Shihua; Hunter, Alan; Wang, Xiangyang; Liu, Dengfeng
ABSTRACT: Bispecific antibodies are an emergent class of biologics that is of increasing interest for therapeutic applications. In one bispecific antibody format, single-chain variable fragments (scFv) are linked to or inserted in different locations of an intact immunoglobulin G (IgG) molecule to confer dual epitope binding. To improve biochemical stability, cysteine residues are often engineered on the heavy- and light-chain regions of the scFv to form an intrachain disulfide bond. Although this disulfide bond often improves stability, it can also introduce unexpected challenges to manufacturing or development. We report size variants that were observed for an appended scFv-IgG bispecific antibody. Structural characterization studies showed that the size variants resulted from the engineered disulfide bond on the scFv, whereby the engineered disulfide was found to be either open or unable to form an intrachain disulfide bond due to cysteinylation or glutathionylation of the cysteines. Furthermore, the scFv engineered cysteines also formed intermolecular disulfide bonds, leading to the formation of highly stable dimers and aggregates. Because both the monomer variants and dimers showed lower bioactivity, they were considered to be product-related impurities that must be monitored and controlled. To this end, we developed and optimized a robust, precise, and accurate high-resolution size-exclusion chromatographic method, using a statistical design-of-experiments methodology.